Islamic Therapeutic Communication in Trauma Recovery of Victims of Sexual Violence at The Technical Implementation Unit of The Aceh Women And Children Protection Area (Uptd Ppa) - putri, tisi maulidya; Kholil, Syukur; Zainun, Zainun (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Abstract                                                                          This research aims to find out how Islamic therapeutic communication is implemented in recovering from trauma from victims of sexual violence at the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA). This paper uses the Stimulus-Organism-Response (SOR) approach. This research uses qualitative methods with descriptive data analysis. Data was obtained through interviews, document study, and observation. The research informants were the Head of the UPTD PPA, Head of the Administration Subdivision, Head of the Case Follow-up Section, Head of the Reception and Clarification Section, Clinical and Forensic Psychologists, Psychological and Legal Counselors, Social Welfare Workers and Foster Mothers. The research results show the implementation of Islamic therapeutic communication in three stages: 1) Islamic Therapeutic Communication in the Orientation or Introduction Phase, 2) Therapeutic Communication in the Working Phase, and 3) Islamic Therapeutic Communication in the Termination Phase which is carried out by service officers at UPTD PPA with good speech, an attitude full of gentleness, adjusting the language and content of the conversation, conveying information about the real situation about the victim's problem, even though it does not completely heal the trauma, it has an effect on self-acceptance, communication skills, and motivation so that the victim gets closer and closer. repent to Allah. Islamic therapeutic communication that is applied prioritizes empathy and building rapport.